Health Care Associated Hematogenous Pyogenic Vertebral Osteomyelitis. Issue 3 (January 2015) - Pigrau, Carlos; Rodríguez-Pardo, Dolors; Fernández-Hidalgo, Nuria; Moretó, Laura; Pellise, Ferran; Larrosa, Maria-Nieves; Puig, Mireia; Almirante, Benito; Snowden., Jessica
<x xml:space="preserve">Abstract</x> Abstract Although hematogenous pyogenic spinal infections have been related to hemodialysis (HD), catheter-related sepsis, and sporadically, to other nosocomial infections or procedures, in most recent studies and reviews the impact of nosocomial infection as a risk factor for vertebral osteomyelitis (VO) is not well established. The aim of our study was to describe the risk factors, infectious source, etiology, clinical features, therapy, and outcome of health care associated VO (HCAVO), and compare them with community-acquired VO (CAVO) cases. A retrospective cohort study of consecutive patients with hematogenous VO was conducted in our third-level hospital between 1987 and 2011. HCAVO was defined as onset of symptoms after 1 month of hospitalization or within 6 months after hospital discharge, or ambulatory manipulations in the 6 months before the diagnosis. Over the 25-year study period, among 163 hematogenous pyogenic VO, 41 (25%) were health care associated, a percentage that increased from 15% (9/61) in the 1987–1999 period to 31% (32/102) in the 2000–2011 period (P < 0.01). The presumed source of infection was an intravenous catheter in 14 (34%), cutaneous foci in 8 (20%), urinary tract in 7 (17%), gastrointestinal in 3 (7%), other foci in 3 (7%), and unknown in 6 (15%). Staphylococcus aureus was the most frequently isolated microorganism (14 cases, 34%), followed by coagulase-negative Staphylococci (CoNS) in 6 (15%), and Enterobacteriaceae in 6 (15%) cases. Compared with CAVO cases, patients with HCAVO were older (mean 66.0 SD 13.0 years vs 60.5 SD 15.5 years), had more underlying conditions (73% vs 50%, P < 0.05), neoplasm/immunosuppression (39% vs 7%, P < 0.005), chronic renal failure (19% vs 4%, P < 0.001), a known source of infection (85% vs 54% P < 0.05), Candida spp (7% vs 0%, P < 0.01) or CoNS infections (15% vs 2%, P < 0.05), higher mortality (15% vs 6%, P = 0.069), and a higher relapse rate in survivors (9% vs 1%, P < 0.05). Presently, in our setting, one-third of hematogenous pyogenic VO infections are health care associated, and a third of these are potentially preventable catheter-related infections. Compared with CAVO, in health care associated hematogenous VO, mortality and relapse rates are higher; hence, further prevention measures should be assessed.